THU0151 Disease Duration and Year of Publication Affect the Results of Studies on Rheumatoid Arthritis Damage Progression by Biologic Agents: A Systematic Review and Meta-Analysis. (23rd January 2014) - Favalli, E. G.; Biggioggero, M.; Pregnolato, F.; Meroni, P. L.
Abstract : Background: Direct head-to-head comparisons among all available biologic agents for efficacy on damage progression in rheumatoid arthritis (RA) have not been conducted. Objectives: To indirectly compare the 12 months effects of available biologic agents in slowing RA radiographic progression. Methods: A systematic review of literature of randomised, double-blind, controlled trials (RCTs) evaluating RA radiographic progression as a primary or secondary endpoint was conducted from Jan 1995 to May 2012. Radiographic progression from baseline, heterogeneity, and effect size (ES [95% CI]) were calculated through a mixed-effect model. Treatment with methotrexate (MTX-experienced or MTX-naïve) before study enrollment and period of study enrolment (PoE) were used as moderators. Results: The PubMed search resulted in 183 references and 14 were eligible for the meta-analysis (the first in 2000, the last in 2011). The analysis of study distribution in ES forest plots showed in both subgroups a high correlation between the study PoE and the impact of biological therapy (figure). In MTX-naïve subgroup, ES was statistically lower for infliximab compared with etanercept (P=0.003), abatacept (P<0.001), rituximab (P=0.001), and golimumab (P=0.023). In the MTX-experienced subgroup, ES was statistically lower for infliximab and etanercept versus abatacept (P<0.001 both) and golimumab (P<0.001 and P=0.018, respectively), and for adalimumab versus abatacept (P<0.001). Image/graph: Conclusions: PoE deeply influences study population propensity to radiographic progression in each trial. This finding does not allow the indirect comparison of various biologic agents, despite our mixed-model significantly reduces heterogeneity among RCTs. References: Rahman MU. Ann Rheum Dis 2011;70:1631–40 Disclosure of Interest: None Declared